DEKONSTRUKSI BUDAYA KEKUASAAN DALAM CA BAU KAN KARYA REMY SYLADO - Asmarani, Ratna (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
The focus of analysis in this paper is about how the power of the powerful is deconstructed by people in the peripheral sphere. The male protagonist, Tan Peng Liang, is a peripheral Chinese man who does not only deconstruct the central power controlled by powerful ruler of different race, but he also deconstructs the power of the Chinese committee officially established by the colonizer. On the other side, Tinung, ca bau kan Jodo River, is a poor, illiterate Javanese woman who deconstructs Tan Peng Liang’s power. Using Derridean deconstructive approach towards the text, it can also be known that the deconstructive attempts applied by Tan Peng Liang tend to be deliberate, full of calculated power, using all means, with the purpose of gaining profit and power. On the other side, Tinung’s deconstructive attempts tend to be accidental, soft and natural, based on the power of the powerless, but have no purpose of gaining profit or power for herself.